Multi-dimensional transcriptome analysis reveals modulation of cholesterol metabolism as highly integrated response to brain injury - Gourain, Victor Philippe Marie; Armant, Olivier; Lübke, Luisa; Diotel, Nicolas; Rastegar, Sepand; Strähle, Uwe (Frontiers in neuroscience, 2021)
Zebrafish is an attractive model to investigate regeneration of the nervous system. Despite major progress in our understanding of the underlying processes, the transcriptomic changes are largely unknown. We carried out a computational analysis of the transcriptome of the regenerating telencephalon integrating changes in the expression of mRNAs, their splice variants and investigated the putative role of regulatory RNAs in the modulation of these transcriptional changes. Profound changes in the expression of genes and their splice variants engaged in many distinct processes were observed. Differential transcription and splicing are important processes in response to injury of the telencephalon. As exemplified by the coordinated regulation of the cholesterol synthesizing enzymes and transporters, the genome responded to injury of the telencephalon in a multi-tiered manner with distinct and interwoven changes in expression of enzymes, transporters and their regulatory molecules. This coordinated genomic response involved a decrease of the mRNA of the key transcription factor SREBF2, induction of microRNAs (miR-182, miR-155, miR-146, miR-31) targeting cholesterol genes, shifts in abundance of splice variants as well as regulation of long non-coding RNAs. Cholesterol metabolism appears to be switched from synthesis to relocation of cholesterol. Based on our in silico analyses, this switch involves complementary and synergistic inputs by different regulatory principles. Our studies suggest that adaptation of cholesterol metabolism is a key process involved in regeneration of the injured zebrafish brain.
Gesehen am 28.02.2022